2020
DOI: 10.3389/fphar.2020.00880
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Attenuates Amyloid-β (Aβ)-Induced Neuronal Insulin Resistance Through PTEN Downregulation

Abstract: Neuronal insulin resistance is implicated in neurodegenerative diseases. Icariin has been reported to improve insulin resistance in skeletal muscle cells and to restore impaired hypothalamic insulin signaling in the rats with chronic unpredictable mild stress. In addition, icariin can exert the neuroprotective effects in the mouse models of neurodegenerative diseases. However, the molecular mechanisms by which icariin affects neuronal insulin resistance are poorly understood. In the present study, amyloid-b (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A recent in vivo study suggested that the promotion effect of ICA on proliferation and differentiation of hippocampal neural stem cells in AD model is related to the BDNF-tyrosine kinase B (TrkB)-ERK/AKT signaling pathway ( Lu et al, 2020 ). Moreover, ICA treatment significantly enhanced proteasome-dependent degradation of PTEN and protected SK-N-MC cells from Aβ-induced insulin resistance ( Zou et al, 2020 ). In addition, by down-regulating the expression of β-site amyloid precursor protein (APP) cleavage enzyme 1, icariin could decrease the deposition of β-amyloid peptide ( Wu et al, 2020 ).…”
Section: Natural Products For Prevention and Treatment Of Alzheimer’s Disease Based On Pi3k/akt Pathawymentioning
confidence: 99%
“…A recent in vivo study suggested that the promotion effect of ICA on proliferation and differentiation of hippocampal neural stem cells in AD model is related to the BDNF-tyrosine kinase B (TrkB)-ERK/AKT signaling pathway ( Lu et al, 2020 ). Moreover, ICA treatment significantly enhanced proteasome-dependent degradation of PTEN and protected SK-N-MC cells from Aβ-induced insulin resistance ( Zou et al, 2020 ). In addition, by down-regulating the expression of β-site amyloid precursor protein (APP) cleavage enzyme 1, icariin could decrease the deposition of β-amyloid peptide ( Wu et al, 2020 ).…”
Section: Natural Products For Prevention and Treatment Of Alzheimer’s Disease Based On Pi3k/akt Pathawymentioning
confidence: 99%
“…Icariin (ICA) is a major constituent of a flavonoid isolated from the plant Herba epimedii. A wide range of pharmacological effects has been attributed to ICA, including: improvement in neuronal insulin resistance Zou et al (2020) and testicular dysfunction (Zhao et al, 2020); protection of hippocampal neurons Liu et al (2019) and nucleus pulposus cells (Hua et al, 2020); potential against Alzheimer's Disease (Angeloni et al, 2019); and notably, as a traditional Chinese medicine, nourishment of the kidney and reinforcement of Yang. Recent research has demonstrated that ICA treatment reduces blood glucose levels in type 2 diabetic rats and protects pancreatic function Han et al (2015), Li et al (2020), Zhang and Qiu (2020), suggesting that ICA has an anti-T2DM effect. However, the exact mechanism of ICA on T2DN is yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Icariin, as a major bioactive component for both Chinese herb and formula has been found to evoke the neuroprotective effects both in vivo and in vitro (Zou et al 2020). For instances, icariin can improve learning dysfunction, and restore synaptic and cognitive deficits in AD mice (Urano and Tohda 2010;Chen et al 2016;Sheng et al 2017).…”
Section: Discussionmentioning
confidence: 99%